TRAPUM upper limits on pulsed radio emission for SMC X-ray pulsar J0058−7218. Issue 4 (10th October 2022) - Carli, E; Levin, L; Stappers, B W; Barr, E D; Breton, R P; Buchner, S; Burgay, M; Kramer, M; Padmanabh, P V; Possenti, A; Venkatraman Krishnan, V; Behrend, J; et al.
ABSTRACT: The TRAPUM collaboration has used the MeerKAT telescope to conduct a search for pulsed radio emission from the young Small Magellanic Cloud pulsar J0058−7218 located in the supernova remnant IKT 16, following its discovery in X-rays with XMM–Newton . We report no significant detection of dispersed, pulsed radio emission from this source in three 2-h L -band observations using the core dishes of MeerKAT, setting an upper limit of 7.0 μ Jy on its mean flux density at 1284 MHz. This is nearly seven times deeper than previous radio searches for this pulsar in Parkes L -band observations. This suggests that the radio emission of PSR J0058−7218 is not beamed towards Earth or that PSR J0058−7218 is similar to a handful of Pulsar Wind Nebulae systems that have a very low radio efficiency, such as PSR B0540−6919, the Large Magellanic Cloud Crab pulsar analogue. We have also searched for bright, dispersed, single radio pulses and found no candidates above a fluence of 93 mJy ms at 1284 MHz.